Ibn Kammūna’s Understanding of the Body - Pattabanoğlu, Fatma Zehra (Nokta Yayın Grubu, 2021)
Ibn Kammūna (d. 1284) is one of the prominent names to have presented the new structuring that emerged after the classical period studies of Islamic philosophy following the 12th century. This article deals with his theory of the body, previously undiscussed in the academic community. The subject has been handled in connection with the philosophy of nature and metaphysics concerning questions such as how the body exists as a possible essence and how the principles guiding this process are reflected in the field of nature, as well as what the body is and what its constituent elements, types, qualities, and additions are. Thus, Ibn Kammūna has been determined to consider the first body to be the first sphere, the later bodies to occur in the process of emanation, and the cause of the body to be the intellect. In addition, he established the body consisting of matter and form to be continuous, to point to itself, and to be an infinitely divisible substance. However, he is observed to have not evaluated matter and form, which are constituent elements of the body, under the category of substance. Moreover, this article also reviews Ibn Kammūna’s approach to the main claims of the Peripatetic and Illuminationist traditions about the body contained in his original works and commentaries. Through the proofs and reasoning made in the details of these claims, Ibn Kammūna is understood to have thought mostly in line with Ibn Sīnā about the definition and essence of the body. He occasionally agreed with Suhrawardī about the properties and additions of the body. This study investigates how Ibn Kammūna shaped Ibn Sīnā’s theory of the body, upon which Suhrawardī had expanded, and whether its content is original in this context. Thus, I aim to contribute to the field by following the processes of change, expansion, and transfer of philosophical accumulation in Islamic thought after these two philosophers who had founded of the Peripatetic and Illuminationist schools.
Keywords: ibn kammūna; BP1-253; accident; body; substance; Islam; matter; form